Mean stop paths and diffusion regimes of molecules in one-dimensional zeolite channels. (23rd November 2017) - Liu, Jichang; Cheng, Zhenfei; Wei, James; Zhang, Qiancheng; Chen, Xiang; Cen, Yuhao; Li, Linfeng
Graphical abstract: Highlights: The diffusion regimes and their boundaries are concisely described by a map. The mean stop path depends on both the mean free path and the diameter difference. MSP can describe the characteristics of molecular motion in a zeolite channel. Abstract: Molecular dynamics methods were used to simulate the diffusion of noble gas molecules, Ne, Ar, and Kr, in the one-dimensional zeolite channels of VET, AFI, VFI, and MCM-41. The gaseous, Knudsen, and configurational diffusion regimes were concisely described by a diffusion regime map. The boundary between the gaseous and the Knudsen diffusion regimes was determined by the probability, Pmm, of bimolecular collision, which was a function of both diameter ratio ( dc /dm ) and volume density ρV . For a molecule in a channel surrounded by other molecules, the concept of mean stop path (MSP) was proposed as the average distance between collisions, either with another molecule or with the channel wall. The MSP depends on both the mean free path and the difference in channel and molecular diameters ( dc - dm ). A theoretical model for calculating MSP of noble gas molecules in one-dimensional zeolite channels was derived based on the additivity of diffusion resistances. The mean stop path can describe the characteristics of molecular motion in a zeolite channel in the same way that mean free path does in an infinite space.